Respuesta :
Answers: Using the process of completing the square:
1. Isolate the constant by adding 7 to both sides of the equation:
x^2-6x-7+7=0+7
x^2-6x=7
2. Add 9 to both sides of x2 – 6x = 7 to form a perfect square trinomial while keeping the equation balanced:
x^2-6x+9=7+9
x^2-6x+9=16
3. Write the trinomial x2 – 6x + 9 as squared:
(x-3)^2 = 16
4. Use the square root property of equality to get x – 3 = ±4 .
sqrt[ (x-3)^2 ] = ± sqrt(16)
x-3 = ±4
5. Isolate the variable to get solutions of –1 and 7.
x-3 = ±4
x-3+3 = ±4+3
x = ±4+3
x1=-4+3→x1=-1
x2=+4+3→x2=7
The correct steps to solve the equation are as follows;
Isolate the constant from the equation adding 7 by both sides of the equation.
Adding 9 to both sides of x2 – 6x = 7 to form a perfect square trinomial while keeping the equation balanced.
Use the square root property of equality to get x – 3 = ± 4.
Given that
Equation; [tex]\rm x^2 - 6x - 7 = 0 [/tex]
According to the question
To solve the given equation follow all the steps given below.
Equation; [tex]\rm x^2 - 6x - 7 = 0 [/tex]
- Step1; Isolate the constant from the equation adding 7 by both sides of the equation.
[tex]\rm x^2 - 6x - 7 = 0 \\ \\ \rm x^2 - 6x - 7 +7 = 0+7\\ \\ \rm x^2 - 6x =7[/tex]
- Step2; Adding 9 to both sides of x2 – 6x = 7 to form a perfect square trinomial while keeping the equation balanced.
[tex]\rm x^2-6x=7\\ \\ x^2 -6x+9 = 7+9\\ \\ [/tex]
- Step3; Write the trinomial x2 – 6x + 9 as (x-3) squared.
[tex]\rm x^2 -6x+9 = 7+9\\\\ (x-3)^2= 16[/tex]
- Step4; Use the square root property of equality to get x – 3 = ± 4.
[tex]\rm (x-3)^2=16\\ \\ (x-3)^2=4^2\\ \\ x-3 = \pm 4[/tex]
- Step5; Isolate the variable to get solutions of –1 and 7.
[tex]\rm (x-3) = \pm 4\\ \\ x-3=4, \ x=4+3, \ x=7\\ \\ x-3=-4, \ x=-4+3, \ x=-1[/tex]
To know more about the Quadratic equation click the link given below.
https://brainly.com/question/3638962